2021
DOI: 10.7717/peerj.10903
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status and quality of life in elderly patients with coronary heart disease

Abstract: Background Coronary heart disease (CHD) is the leading cause of morbidity and mortality among elderly individuals. Patients with CHD are at high risk for mental health disorders, and psychological issues may affect the quality of life (QoL) of these patients. Nevertheless, there is little evidence regarding the psychological issues and QoL of patients with CHD among the elderly population. This study aimed to investigate the relationship between comorbidities and mental status as well as QoL amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
1
3
0
2
Order By: Relevance
“…Chronic complications like heart disease may severely impact on quality of life that may prone elderly subjects to getting depression. In accordance with our findings, Tang et al showed that heart disease was a significant risk factor for mental health disorders in elderly patients [32]. Al et al also showed a positive correlation between depression and heart disease [33].…”
Section: Discussionsupporting
confidence: 92%
“…Chronic complications like heart disease may severely impact on quality of life that may prone elderly subjects to getting depression. In accordance with our findings, Tang et al showed that heart disease was a significant risk factor for mental health disorders in elderly patients [32]. Al et al also showed a positive correlation between depression and heart disease [33].…”
Section: Discussionsupporting
confidence: 92%
“…Chinese version SCL-90 comprises 10 psychiatric factors, namely depression, anxiety, somatization, phobic, paranoid, obsessive compulsive, interpersonal sensitivity, hostility, psychoticism, and other factors such as sleep and diet (20). Each item was scored using a 5-point scale (0=none, 1=slight, 2=mild, 3=moderate, 4=severe) (21). This scale suggested the score of a positive item was more than 2, which may indicate potential mental health issues (20).…”
Section: Chinese Version Scl-90mentioning
confidence: 99%
“…Третий фактор -психическое здоровье и эмоциональное благополучие. У больных возможна скрытая депрессия, которой не всегда уделяют должное внимание [16]. Для пациентов, перенесших ОКС, в отдаленном периоде после реваскуляризации миокарда наиболее важен уровень качества жизни, так как они хотят сохранить функциональную независимость, иметь возможность социального общения, осуществлять активную физическую деятельность и самостоятельно удовлетворять личностные потребности [17].…”
Section: Discussionunclassified
“…M. Tang и соавт. установили взаимосвязь инсульта в анамнезе у пожилых пациентов с ИБС со снижением уровня качества жизни, но по психологическому компоненту здоровья [16]. В нашем исследовании наличие работы до реваскуляризации миокарда у больных, перенесших ОКС, ассоциировано с ростом физического благополучия, что, вероятно, обусловлено исходно лучшими резервно-адаптационными возможностями данных пациентов.…”
Section: Discussionunclassified